Macroeconomic Uncertainty and Bank Lending: The Case of Ukraine - Oleksandr Talavera; Andriy Tsapin; Oleksandr Zholud (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Our study investigates the link between bank lending behavior and macroeconomic uncertainty. We develop a dynamic model of a bank's value maximization that results in a negative relationship between loan to capital ratio and macroeconomic uncertainty. This proposition is tested using a panel of Ukrainian banks collected from NBU and covering the period 2003q1-2005q3. The results indicate that banks increase their lending ratios when macroeconomic uncertainty decreases. We demonstrate that our results are robust with respect to the measurement of macroeconomic uncertainty. The reaction of banks to changes in uncertainty is not uniform and depends on bank-specific characteristics.
Keywords: G28; P34; P27; G21; 330; Banks; macroeconomic uncertainty; Ukraine; banks' balance sheets